Cooperation between companies in the production chain: diagnosis of the productive arrangement of Limeira semi-jewel: diagnose do Arranjo Produtivo de Semijoias de Limeira (Management and Connections Journal, 2023)
This study seeks to contribute to the management area by analyzing the relations of interaction and cooperation between the actors of the semi-jewel cluster in Limeira/SP. The study is characterized as exploratory and descriptive using the techniques of semi-structured interviews with the coordinating body of the APL and a questionnaire for the different actors, in the various stages of the process. The results indicate that the cooperation and interaction between the actors is of low intensity, which in turn act in small groups of affinities and not in a broad and systemic way. Among the factors that evidence this fragmented performance, among the actors, it is identified the existence of strong competition and high level of distrust between the parties. However, despite these negative factors, the actors recognize that the concentration, in one location of companies that cover the stages of the manufacturing process, allows operational and commercial gains.
Keywords: cluster; Competitive advantage; organizational networks